2023
DOI: 10.48550/arxiv.2301.07749
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved methodologies to study the performance of the ANET Compact Neutron Collimator

Abstract: The ANET project aims at developing 2D compact neutron collimators for neutron imaging applications. The results of the ANET collimator performances, presented in this communication, are based on data collected at the FISH beamline at TU-Delft. Two independent methods to evaluate the neutron radiography resolution are described and discussed, as well as a comparison of the beam divergence with or without the ANET collimator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The measurements taken with both Siemens Star and gadolinium knife-edge reference samples have been analysed following the procedure in [2], and the results are shown in figure 2 The expected beam divergence should not be affected by a collimator whose collimation power is smaller than the beam divergence itself. The measurements shown in figure 2 point at different conclusions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The measurements taken with both Siemens Star and gadolinium knife-edge reference samples have been analysed following the procedure in [2], and the results are shown in figure 2 The expected beam divergence should not be affected by a collimator whose collimation power is smaller than the beam divergence itself. The measurements shown in figure 2 point at different conclusions.…”
Section: Resultsmentioning
confidence: 99%
“…The study, here reported, derives its motivation from measurements performed at the TU-Delft FISH beam-line [1], where an unexpected improvement on the quality of the beam collimation [2], beyond what a simple geometrical model could predict, have been shown. This indicates that more complicated effects arise when combining two collimation systems.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations